Public trust in business - Harris, Jared D; Moriarty, Brian T.; Wicks, Andrew C (Cambridge : Cambridge University Press, 2014)
Public trust in business is one of the most important but least understood issues for business leaders, public officials, employees, NGOs and other key stakeholders. This book provides much-needed thinking on the topic. Drawing on the expertise of an international array of experts from academic disciplines including business, sociology, political science and philosophy, it explores long-term strategies for building and maintaining public trust in business. The authors look to new ways of moving forward, by carefully blending the latest academic research with conclusions for future research and practice. They address core drivers of public trust, how to manage it effectively, the consequences of low public trust, and how best to address trust challenges and repair trust when it has been lost. This is a must-read for business practitioners, policy makers and students taking courses in corporate social responsibility or business ethics.
Machine generated contents note: Preface: discovering new territory in public trust in business; Acknowledgements; 1. Public trust in business: what's the problem and why does it matter? Andrew C. Wicks, Brian T. Moriarty and Jared D. Harris; Part I. Trusting the Institution of Business: 2. The economic crisis of 2008, trust in government, and generalized trust Eric M. Uslaner; 3. Too big to trust? Managing stakeholder trust in the post-bailout economy Deepak Malhotra; 4. At the crossroads of trust and distrust: skepticism and ambivalence towards business Robert Bies; 5. Public trust in business and its determinants Kirsten Martin, Michael Pirson and Bidhan L. Parmar; 6. The role of public, relational and organizational trust in economic affairs Karen S. Cook and Oliver Schilke; Part II. Public Trust and Business Organizations: 7. Public trust and trust in particular firm-stakeholder interactions: a theoretical model and implications for management Jared D. Harris and Andrew C. Wicks; 8. Creating more trusting and trustworthy organizations: exploring the foundations and benefits of presumptive trust Roderick Kramer; 9. Building trust through reputation management Paul Argenti; 10. Can trust flourish where institutionalized distrust reigns? Reinhard Bachmann and Edeltraud Hanappi-Egger; 11. Roles of third parties in trust repair: lessons from high tech alliances for public trust Rosalinde Klein Woolthuis, Bart Nooteboom and Gjalt de Jong; 12. The repair of public trust following controllable or uncontrollable organizational failures: a conceptual framework Laura Poppo and Donald J. Schepker; 13. Conclusion: towards a better understanding of public trust in business Jared D. Harris, Andrew C. Wicks and Brian T. Moriarty; Index.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Trust; Public relations; Business ethics; Business -- Public opinion; Corporate culture